Willingness to participate in an HIV vaccine trial : construction and initial validation of the Willingness to Participate Scale (WTPS), and an application and extension of the Theory of Planned Behavior - Fincham, Dylan Shaun (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2008.